INNOVATIVENESS AS ANTECEDENTS TO FIRM PERFORMANCE: THE MEDIATING ROLE OF COMPETITIVE ADVANTAGE AND SUPPLY CHAIN FLEXIBILITY OF MANUFACTURING FIRMS - Mee-ngoen, Benjabhon; Mee-ngoen, Benjabhon; Sirariyakul, Tussanee; Sirariyakul, Tussanee; Limphothong, Sugris; Limphothong, Sugris; Tomcharoen, Narong; Tomcharoen, Narong; Jermsittiparsert, Kittisak; Jermsittiparsert, Kittisak (International Journal of Supply Chain Management, 2020)
The study has examined the impact of the innovative capability on the firm performance of Indonesian manufacturing firms The current study aimed to examine the role of competitive advantage and SCH flexibility as a mediator on the financial performance and intellectual CAP nexus, in the Indonesia?s manufacturing industry. the response rate for this survey is 59.6%. The results in this study suggest a number of issues which must be addressed by the researchers and managers. Therefore, assessing the third variable is vital to have a meaningful interpretation of the association among study variables. In a study, if a relationship does not take into account the mediating mechanism, then it fails to get complete understanding of the relationship. In addition, failing to consider the effect of a mediator may not have clear explanation of the relationship outcome. Contrarily, a model which considers the mediating mechanism is likely to estimate accurate relationship among variables under study. Therefore, in order to reach to the legitimate conclusions and decisions, the practitioners and scholars must consider the significance of competitive advantage on performance and intellectual capital (CAP) nexus. Hence, results might facilitate the management for taking initiatives to develop acceptance and greater understanding of the intellectual CAP, thereby boosting organizations? performance as well as their competitive position.